The effect of restrictions in interest on indigenous land market in Kuala Lumpur - : an institutional economics perspective - Ismail Omar, 1962-; Pasific Rim Real Estate Society (PRRES) Conference (7th : 2001 : Adelaide) (Skudai : Universiti Teknologi Malaysia, 2001)
28